2015
DOI: 10.1515/jppr-2015-0045
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol oxidase and lysozyme mediate induction of systemic resistance in tomato, when a bioelicitor is used

Abstract: Tomato (Solanum lycopersicum L.) is attacked by Pseudomonas syringae pv. tomato causing heavy damage to the crops. The present study focused on the application of aqueous fruit extracts of neem (Azadirachta indica L.) on a single node of aseptically raised tomato plants. Observations were done, and the changes in the activity and isoenzyme profile of polyphenol oxidase (PPO) and lysozyme, both at the site of treatment as well as away from it, were noted. The results demonstrate that neem extract could signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
10
0
2
Order By: Relevance
“…These results were concomitant with several studies that confirmed that many plants extracts have defense enzymes stimulation properties. Goel and Paul [ 58 ] found that the PPO in tomato was stimulated by Azadirachta indica aqueous fruit extracts. Additionally, PAL, POD and PPO in cotton were activated by zimmu ( Allium cepa L. and Allium sativum L.) [ 59 ], and PAL in barely prompted by aqueous extract of leaves of Azadirachta indica [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results were concomitant with several studies that confirmed that many plants extracts have defense enzymes stimulation properties. Goel and Paul [ 58 ] found that the PPO in tomato was stimulated by Azadirachta indica aqueous fruit extracts. Additionally, PAL, POD and PPO in cotton were activated by zimmu ( Allium cepa L. and Allium sativum L.) [ 59 ], and PAL in barely prompted by aqueous extract of leaves of Azadirachta indica [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The same samples used for H 2 O 2 quantification were used for SOD, POD, and MDA activity analysis. Total SOD, POD, and MDA activity was measured using previously described methods [ 58 , 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…The antifungal activity of medicinal plant extracts against the fungal pathogens may be due to indirect effects on host plants such as induction of host plant immune systems against pathogens (Abkhoo and Jahani, 2017). Also, other responses of medicinal plant include; induced defense-related genes, pathogenesis-related (PR) proteins, accumulation of phytoalexins, and deposition of lignin and programmed cell death (Goel and Paul, 2015). POX considered ones for important group of enzymes involved in plant resistance mechanisms, such as synthesis of phenolic compounds and the formation of structural barriers (Dalisay & Kuć, 1995).…”
Section: Biochemical Analysismentioning
confidence: 99%